Study on English Translation Skills from a Cross Cultural Perspective - Wang, Yuan (Transactions on Social Science, Education and Humanities Research, 2024)
This article explores English translation techniques from a cross-cultural perspective, and conducts in-depth analysis from cultural differences, language habits and expressions, homophones, idioms, and cultural metaphors. It reveals the complexity and importance of cross-cultural translation and proposes corresponding translation strategies and techniques. Combined with practical case analysis, it highlights the cross-cultural challenges and solutions in advertising translation and interpretation.